Fourteenth General Review of Quotas : The Size of the Fund. (Policy Papers; Policy Paper, 2010)
The FY 11-13 medium-term budget (MTB) presented in this paper brings to a close the three-year restructuring effort that began with the FY 09-11 MTB. It secures savings of USD 100 million in real terms while providing sufficient financing for structural operations and the Fund's response to the global financial crisis. This budget has been crafted in a period of uncertainty regarding the final scope and duration of the financial crisis as well as the ongoing responsibilities that the Fund may retain even as the crisis unwinds. There is also uncertainty about new responsibilities that may result as a review of the Fund's mandate is undertaken. Addressing these items will be part of the work agenda to be undertaken in the coming year.